Teachers’ Implementation of Higher Order Thinking Skills in Physical Education in an Online-Based Professional Teacher Education Programme - Sefri Hardiansyah (Journal of Learning for Development)
Teacher Professional Education (known as PPG) is an Indonesian government programme to produce professional teachers who can implement Higher-Order Thinking Skills (HOTS) in learning so that students in Indonesia can be expected to have high HOTS. However, in reality, students' HOTS in Indonesia are still low, raising questions about the effectiveness of PPG in producing teachers who can implement HOTS. This study aimed at investigating the implementation of HOTS in physical education learning by teachers who participated in the online PPG programme based on gender and tenure, so that it can be a benchmark by the Indonesian government for the effectiveness of the PPG programme. This was a comparative study and the population was comprised of 35 physical education teachers who participated in the PPG programme online at Padang State University in 2022 Batch I. The research sample of 30 people was determined by the purposive sampling technique. HOTS implementation data was taken from video documentation of participants' teaching practice and then assessed using 19 items of the Teaching Performance Guidelines. Data were analysed with an independent sample t-test and ANOVA test. The results showed that physical education teachers who participated in the online-based PPG programme were able to implement HOTS into the learning process well, and the implementation of HOTS, based on gender and tenure, was not significantly different.